Evidence‐ and consensus‐based (S3) Guidelines for the Treatment of Actinic Keratosis – International League of Dermatological Societies in cooperation with the European Dermatology Forum – Short version. (14th September 2015) - Werner, R.N.; Stockfleth, E.; Connolly, S.M.; Correia, O.; Erdmann, R.; Foley, P.; Gupta, A.K.; Jacobs, A.; Kerl, H.; Lim, H.W.; Martin, G.; Paquet, M.; et al.
Abstract Background Actinic keratosis (AK) is a frequent health condition attributable to chronic exposure to ultraviolet radiation. Several treatment options are available and evidence based guidelines are missing. Objectives The goal of these evidence‐ and consensus‐based guidelines was the development of treatment recommendations appropriate for different subgroups of patients presenting with AK. A secondary aim of these guidelines was the implementation of knowledge relating to the clinical background of AK, including consensus‐based recommendations for the histopathological definition, diagnosis and the assessment of patients. Methods The guidelines development followed a pre‐defined and structured process. For the underlying systematic literature review of interventions for AK, the methodology suggested by the Cochrane Handbook for Systematic Reviews of Interventions, the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) statement and Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology was adapted. All recommendations were consented during a consensus conference using a formal consensus methodology. Strength of recommendations was expressed based on the GRADE approach. If expert opinion without external evidence was incorporated into the reasoning for making a certain recommendation, the rationale was provided. The Guidelines underwent open public review and approval by the commissioning societies. Results Various interventions for the treatment of AK have been assessed for their efficacy. The consenting procedure led to a treatment algorithm as shown in the guidelines document. Based on expert consensus, the present guidelines present recommendations on the classification of patients, diagnosis and histopathological definition of AK. Details on the methods and results of the systematic literature review and guideline development process have been published separately. Conclusions International guidelines are intended to be adapted to national or regional circumstances (regulatory approval, availability and reimbursement of treatments).